Topical Powder Mix of Chalcanthite, Alum, and Clove as an Effective Feet Odor Treatment - Baker, Amera G. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2018)
Treating foot Odor infected with pathogenic fungus and bacteria has been a major concern for pharmaceutical companies. Finding a right treatment with minimum side effects has been of particular importance. This study configures a homemade topical powder mix in treating foot odor. The homemade topical powder mix is free of any harmful chemical constituents; its main constituents being Chalcanthite, Alum, and Clove. Energy dispersive X-ray fluorescence was used for the determination of the chemical composition component of Chalcanthite, Alum, Clove, and the powder mix of Chalcanthite, Alum, and Clove. XRF was able to measure elements such as Oxygen, Sulfur, Aluminum, Potassium, and Copper in kα line. The antimicrobial activity of the powder mix of Chalcanthite, Alum, and Clove was studied against two pathogenic fungi, which are Epidermophyton sp., and Trichophyton sp., and two pathogenic bacteria, which are Brevibacterium sp., and Staphylococcus sp. Screening for antibacterial and antifungal was done using agar disk diffusion. The growth inhibition zone measured ranged from 16 to 28 mm for all the sensitive fungal, and ranged from 14 to 27 mm for the sensitive bacteria.